2009
DOI: 10.1016/j.cognition.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The plasticity of near space: Evidence for contraction

Abstract: The distinction between near space and the space farther away has been well established, as has the relation of this distinction to arm length. Recent studies provide evidence for the plasticity of near space, showing that it is possible to expand its extent ("size") through tool-use. In the present study, we examine the converse effect, whether contraction of near space results from increasing the effort involved on a line bisection task. Adult participants bisected lines at different distances, while, in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 32 publications
5
75
2
1
Order By: Relevance
“…This indicates that bias shifted rightwards with increased viewing distance, consistent with previous results using the landmark task (Bjoertomt et al, 2002;McCourt & Garlinghouse, 2000) and line bisection task (Gamberini et al, 2008;Longo & Lourenco, 2006Lourenco & Longo, 2009;Lourenco et al, 2011;Varnava et al, 2002). Behavioural data from landmark judgments.…”
Section: Behavioural Datasupporting
confidence: 79%
See 4 more Smart Citations
“…This indicates that bias shifted rightwards with increased viewing distance, consistent with previous results using the landmark task (Bjoertomt et al, 2002;McCourt & Garlinghouse, 2000) and line bisection task (Gamberini et al, 2008;Longo & Lourenco, 2006Lourenco & Longo, 2009;Lourenco et al, 2011;Varnava et al, 2002). Behavioural data from landmark judgments.…”
Section: Behavioural Datasupporting
confidence: 79%
“…Studies investigating line bisection in near and far space have typically found a small leftward bias in near space and a (somewhat larger) rightward bias in far space (e.g., Ferrè et al, 2013;Gamberini et al, 2008;Longo & Lourenco, 2006Lourenco & Longo, 2009;Lourenco et al, 2011;Varnava et al, 2002). In contrast, studies using the landmark task have found a leftward bias in near space and a smaller leftward bias (or no bias at all) in far space (e.g., Bjoertomt et al, 2002Bjoertomt et al, , 2009McCourt & Garlinghouse, 2000; this study).…”
Section: Differences Between Landmark and Bisection Taskscontrasting
confidence: 48%
See 3 more Smart Citations